The optimal true ileal digestible lysine requirement for 22 to 45 lb pigs - Lenehan, N.A.; Usry, J.L.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,440 pigs (initially 22.5 lb and 21 d after weaning) was used in a 21-d growth assay to determine the optimal lysine level to maximize growth performance of 22- to 45-lb pigs. Pigs were fed one of five dietary treatments with increasing dietary lysine (1.1, 1.2, 1.3, 1.4 and 1.5% true digestible lysine). All diets had the same soybean meal level with crystalline amino acids added to achieve the increasing lysine levels while maintaining a minimum ratio of all other amino acids to lysine. Average daily gain and feed efficiency improved linearly (P<0.01) with increasing dietary lysine. Although the response to lysine was linear (P<0.01), it would appear that pigs weighing between 22 and 45 lb require approximately 1.4% true digestible lysine (1.54% total lysine) to maximize growth performance.
Keywords: Pigs; Lysine; Growth; Swine